Identifying the Trends and Consequences of Retention Rates among Bachelor Students in Makawanpur Multiple Campus - Chhatkuli, Shyam Bahadur; Aryal, Uttam; Shrestha, Suresh; Nyaupane, Ramji Prasad (International Research Journal of MMC, 2023)
The prime purpose of this study was to successfully examine the trends of drop out in Makawanpur Multiple Campus students studying in bachelor and the consequential effects that would spoil the academic progress of the campus. The data collected from the campus were analysed descriptively from the sample size that included the drop out students of the Makawanpur Multiple Campus in three years. The research method used was analytical which typically use the correlation and regression due to its suitability to determine the strength and direction of the relationship between the variables being studied. The results of this study provide valuable insights into exploring the trend of leaving study among bachelor students and may be used to reflect the consequence which may occur in the near future. It also suggests the strategies for improving retention rates in the different programs of the campus. Overall, this study contributes to overcome the issues that influence student retention and the effectiveness of interventions aimed at improving retention in higher education.